Designing Talent Management System For Increasing Employee Motivation At PT Dirgantara Indonesia (The Indonesian Journal of Business Administration, 2021)
To face world / global competition, the development of Human Capital must be a major concern. The Government of the Republic of Indonesia, puts HC development towards the technology & information era as the first priority in the 5 Priorities for 2019-2024. The HC development program is also a top priority for the Ministry of BUMN, especially in training the workforce and maintaining quality talents in Indonesia as well as creating an inclusive environment for talent in leadership. This is also in line with the BUMN Defense Industry cluster in the HC sector, namely forming ""Human Capital Excellence"". In addition, a talent management system is needed by PTDI to carry out and achieve the company strategy set forth in the 2020-2024 RJPP and subsequent periods. PTDI has experienced delays in the regeneration process resulting in age and competency gaps so that acceleration is needed in talent development so that the leadership relay can run well and sustainably. For this reason, strategic steps are needed in developing human capitals, especially the talent management system, which includes the talent management business process, mapping and analysis of assessment results, succession planning, and talent development programs at every level from the lowest job target position to the Director (BOD) job target. The talent development program consists of the Company's internal development program through job assignments, internal mobility, and coaching & mentoring as well as talent development through the intercompany external coach program through the Defense Industry cluster and the Indonesian Institute of Defense & Technology (IIDT)Keywords : competency gaps, accelerations, talent management systems.